Enhancing Students' Hard Skills in Preparing Financial Statements in Accordance with Financial Accounting Standards for Micro, Small, and Medium Enterprises Using Excel Applications: Peningkatan Hard Skill Siswa Dalam Menyusun Laporan Keuangan Sesuai Standar Akuntansi Keuangan Entitas Mikro Kecil Menengah Dengan Aplikasi Excel - Challen*, Auliffi Ermian; Ismail , Verni Yuliaty; Faisal, Muhammad (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2025)
Preparation of financial statements must be in accordance with applicable financial accounting standards. Financial Accounting Standards for Micro, Small, and Medium Entities (FAS for MSME) is one of the financial accounting standards that is simple and easy to implement by MSMEs. Graduates of Vocational Accounting Department who later work in MSMEs are expected to be able to assist MSMEs in making financial reports according to standards. Community service aims to build students' awareness of the importance of FAS for MSME, to provide knowledge about the rules in FAS for MSME, to prepare financial reports, and to utilize and use excel-based technology to make financial reports according to FAS for MSME. This training starts from the preparation stage, namely a preliminary survey, determining the schedule, and preparing the training. The implementation stage is the implementation of training activities in the form of material and practice as well as participant evaluation in the form of pre-test post-test assessment and practice results. Furthermore, the final stage is the evaluation of training and the preparation of reports and outcomes. The training was conducted using training and mentoring methods for students majoring in accounting to prepare financial reports according to FAS for MSME with excel applications. This training activity was held in the hall and computer laboratory of SMKN 44 Jakarta. The training was attended by 34 students. This community service activity runs smoothly and has achieved its goals. This is indicated by the results that 100% of students have obtained an increase in hardskill competencies, namely being able to prepare financial reports according to FAS for MSME using the excel application